The Hat - Brett, Jan; Nang ChanYeema (New York, USA Scholastic Inc., 1997)
The silly story of a hedgehog who gets a stocking caught on his head. The other farm animals make fun of him but he says it's a hat. At the end hedgie see all the animals have run to the clothesline to get a hat for themselves.
Keywords: Story Collection